Attention Deficit Hyperactivity Disorder: an Aboriginal perspective on diagnosis and intervention. (10th July 2017) - Loh, Pek-Ru; Hayden, George; Vicary, David; Mancini, Vincent; Martin, Neilson; Piek, Jan P.
Abstract : Attention Deficit Hyperactivity Disorder (ADHD) arising from a Western health model has generated much global debate about its relevance in Indigenous communities. More importantly, it has raised questions concerning acceptance of its diagnosis and intervention, hence affecting early identification and treatment compliance. The current study explored an Aboriginal perspective of diagnosis and treatment compliance of ADHD in an Australian Aboriginal community. Using a qualitative approach, 27 participants aged between 22 and 52 years from a Western Australian metropolitan Aboriginal community comprising community members, Aboriginal mental health and education professionals, and Aboriginal parents of children with ADHD, were interviewed either individually or in groups. Participants identified differences in child rearing practices, expectation of child behaviour in school, higher tolerance of hyperactive behaviour within the Aboriginal community and lack of information about ADHD as the main reasons for parents not seeking medical help for the child. Participants also saw the changes in a child's behaviour after medication as a loss of identity/self and this was reported to be the main contributor to treatment non-compliance. Overall, most participants recognised the detrimental effect of having ADHD. However, the current diagnostic process and treatment are not culturally appropriate to assist the Aboriginal community to effectively manage this disorder in their children.